Charity for “Jihad” in Syria : The Indonesian-Uyghur Connection - Soliev, Nodirbek (2020)
A jihadist-aligned Indonesian fundraising group, the Abu Ahmed Foundation (AAF), has been developing close connections with Uyghur and Central Asian fighters in Syria. This link could become a vector for fighters to exit from Syria, and a source of potential risks to Southeast Asia.